1996
DOI: 10.1111/j.1440-1746.1996.tb00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Echo‐Doppler measurements of portal vein and superior mesenteric artery blood flow in humans: Inter‐ and intra‐observer short‐term reproducibility

Abstract: The reproducibility of echo‐Doppler measurements of portal vein and superior mesenteric artery blood flow has not been extensively studied. In the present study, two groups of subjects were examined to test inter‐ and intra‐observer reproducibility. Each study population consisted of 15 non‐portal hypertensive and 15 portal hypertensive subjects. With a standardized technique, the cross‐sectional area and velocity of blood flow in the portal vein and superior mesenteric artery were recorded in triplicate by sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 26 publications
1
36
1
Order By: Relevance
“…The blood supply to the anterior chest wall, besides IMA, is also derived from several other arteries which however cannot be measured with the existed CDU methods because of their fine anatomy and thus they were not included in the present study. Sevastik et al [1,2] suggested the asymmetric increase of blood supply to the left anterior chest wall as a possible cause of right-convex idiopathic scoliosis in girls, while recent studies with CDU [3][4][5] in these individuals doubted this theory of asymmetry because they did not find any asymmetry in blood supply to the anterior chest wall. However, all these studies did not investigate the evolution of blood supply to the anterior chest wall of the female adolescent scoliotics.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…The blood supply to the anterior chest wall, besides IMA, is also derived from several other arteries which however cannot be measured with the existed CDU methods because of their fine anatomy and thus they were not included in the present study. Sevastik et al [1,2] suggested the asymmetric increase of blood supply to the left anterior chest wall as a possible cause of right-convex idiopathic scoliosis in girls, while recent studies with CDU [3][4][5] in these individuals doubted this theory of asymmetry because they did not find any asymmetry in blood supply to the anterior chest wall. However, all these studies did not investigate the evolution of blood supply to the anterior chest wall of the female adolescent scoliotics.…”
Section: Discussionmentioning
confidence: 87%
“…However, all these studies did not investigate the evolution of blood supply to the anterior chest wall of the female adolescent scoliotics. The present study is advantageous to previous studies [3][4][5] because it is prospective, controlled, and used radiographic and CDU-data derived from two consequent measurements within a 2-year period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations